Remote laboratory classes in a COVID pandemic situation. Example of subjects: Microcontroller programming and electronic circuits - Raczyński, Michał (International journal of electrical engineering & education, 2021)
The article presents the possibility of conducting remote laboratory classes in subjects that require the use of specialized equipment (which the student does not have at home). The article is based on the example of classes in microcontrollers programming and electronic circuits. The methods with the use of simulation programs and an innovative approach enabling work on real equipment are presented. The solutions presented in the article were practically and successfully implemented in connection with the coronavirus pandemic in spring 2020 at the Faculty of Electrical Engineering of West Pomeranian University of Technology in Szczecin. A very important feature of the presented ideas is the possibility to adapt the already existing stationary solutions to remote work and use free applications. The characteristic feature of the presented ideas is also simplicity. These two features make it possible to implement remote learning quickly and at a low-cost. Classes conducted using the described system for a group of about 50 students were positively evaluated by them. Their opinions were also included in the article.